The Role of Organizational Justice in Nurses and Midwives' Satisfaction with Performance-Based Payment (Qasedak Project) in Zanjan Educational Hospitals - Jalili, Roya; Asefzadeh, Saeed; Shoghli, Alireza; Mohebi, Mahnaz (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Performance-based payment makes rewards and outcomes result in paid satisfaction , which leads to the success and promotion of employee value and alignment with organizational goals in the light of organizational justice. Objectives: This study aimed to assess The role of organizational Justice in Nurses and Midwives' Satisfaction with Performance-Based Payment (Qasedak Project) in Zanjan Educational Hospitals Methods: This descriptive cross-sectional correlation study was conducted on 149 nurses and midwives in educational hospitals with Cochran formula. The researcher-made questionnaires of satisfaction based on P4P and organizational justice of Moorman and Niehoff were used, and data were analyzed using SPSS software and descriptive and analytic statistics (independent t-test, regression, analysis of variance, and nonparametric Spearman correlation coefficient and cross-tabulation). Results: Nurses and midwives reported moderate organizational justice with an average of 55.7 and low merit pay satisfaction with an average of 13. There was a positive and significant correlation between organizational justice and job satisfaction (r = 0.65), the amount of merit pay and satisfaction (r = 0.33), and organizational justice and the amount of merit pay (r = 0.23). The results revealed that organizational justice with a standard beta of 0.58 had a positive effect on the satisfaction with the merit pay received and alone accounted for 33% of the changes. Conclusion: Since there was a positive and direct correlation between organizational justice and nursing and midwifery staff satisfaction, it is recommended that managers accomplish exact and accurate evaluation of staff performance by means of increasing staff's awareness of Qasedak project, providing timely feedback to them, and observing justice in the payment of rewards.